Aksesibilitas Pembelajaran Kimia di Sekolah Menengah Atas - Ristiyanti, Sinta (INKLUSI, 2020)
This study aims to assess the accessibility of chemistry learning in high school from the perspective of students with disabilities. The research involved three student participants and students with disabilities, as well as chemistry teachers as participants. Data is collected by a non-structured in-depth interview. The data obtained were then processed using data reduction techniques, data exposure, and concluding. The results showed that students with disabilities have a reasonably good perspective on learning chemistry in high school. According to students with disabilities, studying chemistry in high school is easy if the learning environment is supportive and the learning process is accessible. Research also shows that some aspects of chemistry learning in high school are accessible. [Penelitian ini bertujuan menilai aksesibilitas pembelajaran kimia di SMA menurut perspektif siswa difabel. Penelitian melibatkan tiga peserta siswa dan mahasiswa difabel, serta guru kimia sebagai partisipan. Data diperoleh dengan wawancara mendalam yang tidak terstruktur. Data yang diperoleh kemudian diolah dengan menggunakan teknik reduksi data, pemaparan data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa peserta didik dan mahasiswa difabel memiliki perspektif yang cukup baik terhadap pembelajaran kimia di SMA. Menurut para difabel, belajar kimia di SMA itu mudah apabila lingkungan belajarnya mendukung dan adanya pemenuhan aksesibilitas dalam pembelajaran. Penelitian juga menunjukkan bahwa sebagian aspek pembelajaran kimia di SMA sudah aksesibel.]